1998
DOI: 10.1253/jcj.62.626
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Ball Valve Endocarditis due to Gemella Species

Abstract: A case is presented of endocarditis that was affecting a prosthetic ball valve (Starr-Edwards) and which was caused by Gemella species. A 57-year-old man was admitted with a 3-day history of abdominal pain with fever. At the time of admission, his temperature was 37.7°C and laboratory tests showed elevated inflammatory parameters and an increased neutrophil count. However, transthoracic echocardiogram showed no vegetation. During hospitalization, Gemella spp. were detected by blood culture, and a transesophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A summary of laboratory tests is found in Table 3. All population groups showed anemia, [16][17][18]23,24,27,28,[32][33][34][35][36]41,44,46,49 [14,15,[18][19][20][21][22]24,30,31,33,39,[41][42][43]48,49,52,56,68,70,71,73,75,76,78,79,82,86,90] The mitral valve was the most common location of vegetation in the pediatric and geriatric populations, whereas the aortic valve vegetation predominated in the adult age group. Gemella haemolysans, Gemella bergeriae, Gemella sanguinis were mainly found on aortic valves [15-17,19-22,29,30, 33,34,38,39,43,44,49,52,54,56,57,59-61,63,68,6...…”
Section: Laboratory Testsmentioning
confidence: 99%
See 3 more Smart Citations
“…A summary of laboratory tests is found in Table 3. All population groups showed anemia, [16][17][18]23,24,27,28,[32][33][34][35][36]41,44,46,49 [14,15,[18][19][20][21][22]24,30,31,33,39,[41][42][43]48,49,52,56,68,70,71,73,75,76,78,79,82,86,90] The mitral valve was the most common location of vegetation in the pediatric and geriatric populations, whereas the aortic valve vegetation predominated in the adult age group. Gemella haemolysans, Gemella bergeriae, Gemella sanguinis were mainly found on aortic valves [15-17,19-22,29,30, 33,34,38,39,43,44,49,52,54,56,57,59-61,63,68,6...…”
Section: Laboratory Testsmentioning
confidence: 99%
“…Five studies, however, demonstrated antibiotic resistance, in particular penicillin, [49,62] aminoglycoside [49] and fluoroquinolone. [41,62] In studies where patients survived the course of treatment, more patients showed clinical improvement after receiving six weeks or more of antibiotic therapy [16,19,21,25,[30][31][32][33][34]38,39,41,[47][48][49][50][51]55,57,62,66,67,71,72,76,80,82,87,89] than patients who received under six weeks of antibiotic therapy, [15,23,24,27,[35][36][37]46,52,53,58,59,61,63,65,…”
Section: Management Of Endocarditismentioning
confidence: 99%
See 2 more Smart Citations
“…It has been implicated in several diseases primarily in adults, including meningitis and septic shock but rarely IE. [1314] The genus currently includes six subspecies that cause similar clinical illness: morbillorum, haemolysans , bergeriae , sanguinis , palaticanis , and cuniculi , in addition to other subspecies that are restricted to animals. [15] Gemella morbillorum was initially thought to be part of the genus Streptococcus until 1988 when it was found to be related to G. haemolysans at the genus level.…”
Section: Introductionmentioning
confidence: 99%